Revitalizing the Function of Hadith as a Social Instrument in Preventing Divorce in the Modern Era - Rois Hamid Siregar; Sulaiman Muhammad Amir; Muhammad Ali Azmi Nasution (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Divorce in the modern era shows a worrying upward trend, marked by the weakening of the family institution due to a crisis of communication, individualism, and minimal understanding of religion. The Hadith, as one of the main sources of Islamic teachings, contains many social principles that have great potential in maintaining the integrity of the household. Revitalizing the social function of hadith is crucial to make it a preventive instrument in preventing divorce. This study aims to re-examine the role of hadith as a source of social values in building family resilience amidst the challenges of modernity. The method used is a qualitative study based on a thematic approach. The results of the study show that the hadiths of the Prophet not only present normative solutions but also contain social values such as deliberation, patience, empathy, and forgiveness that are highly relevant to the dynamics of contemporary households. In addition, hadith also functions as an ethical guideline that can direct married couples to harmonious communication patterns, fair social roles, and a spiritual understanding of the meaning of marriage. In conclusion, revitalizing hadith as a social instrument not only revives the teachings of the Prophet but also builds household resilience based on prophetic values that are applicable in the modern era.